Physiology of abscission and crop regulation in cotton -a review - Kaur, Ramanjit; ., Rajni; Deol, J.S.; Dass, Anchal (Annals of Agricultural Research, 2016)
Abscission of flowers, squares and bolls is an important problem which causes considerable lint yield loss in cotton. This problem needs to be addressed to obtain optimal yields. Abscission can be regulated by manipulation of the environment or by application of chemicals. The factors, like moderate temperature, moderate water supply, normal light intensities, adequate mineral nutrients, freedom from diseases and insects tend to prevent or delay abscission. Growth retardants, like mepiquat chloride (MC) and cycocel (CCC) reduce internode length, thereby, reducing plant height and stimulating the translocation of photosynthates towards sink. MC 50 ppm sprayed at 90 DAS (days after sowing) resulted in significantly higher yield (11.9 %) over control. Late opening of mature bolls is also one of the major factors limiting crop productivity. Cotton hybrids usually attain excessive vegetative growth and thick crop canopy with poor boll opening especially when crop encounters low temperature at maturity. The use of chemical defoliants has been reported to enhance boll opening without affecting the seed cotton yield. Ethephon and thiadiazuron application at 60% boll opening stage increased the shedding of leaves, boll opening and seed cotton yield.